Characterizing Multiband Optical Emission and Variability of 1ES 1215+303 on Diverse Timescales - A. Ozdonmez; H. Er; M. Tekkesinoglu; E. Ege; M. E. Kenger; I. C. Ozkesen; A. Polatoğlu (The Astrophysical Journal)
This study presents analyses of the optical variability of the 1ES 1215+303 on diverse timescales using multiband observations, including observations in the optical BVRI bands carried out with the 0.6 and 1.0 m telescopes located at the Tübitak National Observatory (TUG) from 2022 to 2024 and Zwicky Transient Facility (ZTF) gri data from 2018 to 2023. Investigation of variability on intraday timescales revealed amplitudes of 4.0% and 5.6% on two nights, with a calculated duty cycle of 63%. We determined a minimum timescale of ~92 minutes from these observations, leading us to limit the radius for the optical emission region and the mass of the black hole. The blazar exhibits moderate short- and long-term variability, with variability amplitudes reaching up to 120% and decreasing as the wavelength shortens. Correlation analysis revealed a strong correlation between the optical multiband emissions without any time lag. Analysis of 109 nightly spectral energy distributions yielded spectral indices ranging from 0.772 to 1.413. The consistent trend of both spectral indices and color with respect to brightness suggests a mild bluer when brighter trend persists throughout the observation period, in contrast to the intraday timescale. Utilizing the weighted wavelet z -transform and Lomb–Scargle methods, we analyzed recurrent optical emission patterns on the combined R -band light curves from TUG, ZTF, and Tuorla observations, revealing a quasiperiodic signal at around 1000 days and a secondary signal at approximately 300 days. These signals were found to be insignificant after accounting for the stochastic process and the trial factor.